Synthesis of Cationic Pd(II) Complexes with 5-Membered Ring Chelating Iminoylcarbene Ligand and Its Catalytic Activity on Norbornene Polymerization - Ali, Roushown; Chandra, Jubaraj; Hasan, Tariqul (Asian Journal of Chemistry, 2019)
Iminoyl N-heterocyclic carbine ligand with cationic allyl Pd(II) complex (3) was successfully synthesized by transmetallation of corresponding Ag complex with one equivalent of [Pd(allyl)(COD)]+SbF6–. A slightly distorted square planer structure of the Pd(II) complex 3 was confirmed by single crystal X-ray diffraction analysis. The Pd(II) complex 3 is stable in air and found to show moderate activity in the polymerization of norbornene without any activator. The polynorbornene produced with Pd(II) complex 3 was obtained to be stable up to 440 °C. The 1H and 13C NMR spectra of the polymer indicated addition polymerization of norbornene and the presence of the vinylene group at the end of polymer chain.